Recognizing the City's Historical Potential Through Drawing Group Activities in Majalaya, Bandung Regency - Diani Apsari; Nisa Eka Nastiti; Patra Aditia (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Majalaya has potential in terms of a creative ecosystem that needs to be developed. From the results of preliminary research that has been done before, this creative ecosystem includes the potential of art-culture, culinary, textiles and history. Related to historical potential, it was also found that in Majalaya there are historical buildings that have a close connection with the culture and history of Majalaya City. This is the background for the Telkom University DKV team to collaborate in carrying out this Community Service activity with Majalaya.id. Majalaya.id itself is an independent news agency with a global-local (glocal) spirit, moving the public to interact in various spaces in Majalaya. On this basis, in this service, the team held a watercolor workshop entitled "Menggambar Majalaya - Workshop & Live Drawing Heritage" which aims to encourage community spirit, especially school children to work while recognizing the historical potential that exists in Majalaya.